Detecting Infections Rapidly and Easily for Candidemia Trial, Part 2 (DIRECT2): A Prospective, Multicenter Study of the T2Candida Panel. (9th February 2018) - Clancy, Cornelius J; Pappas, Peter G; Vazquez, Jose; Judson, Marc A; Kontoyiannis, Dimitrios P; Thompson, George R; Garey, Kevin W; Reboli, Annette; Greenberg, Richard N; Apewokin, Senu; Lyon, G Marshall; Ostrosky-Zeichner, Luis; et al.
Abstract : T2Candida, a nanodiagnostic panel that detects Candida directly within whole blood, was 89% sensitive for diagnosing candidemia at the time of positive blood cultures. In patients who received antifungal therapy, T2Candida identified bloodstream infections that were missed by blood cultures. Abstract: Background: Blood cultures are approximately 50% sensitive for diagnosing invasive candidiasis. The T2Candida nanodiagnostic panel uses T2 magnetic resonance and a dedicated instrument to detect Candida directly within whole blood samples. Methods: Patients with Candida albicans, Candida glabrata, Candida parapsilosis, Candida tropicalis, or Candida krusei candidemia were identified at 14 centers using diagnostic blood cultures (dBCs). Follow-up blood samples were collected concurrently for testing by T2Candida and companion cultures (cBCs). T2Candida results are reported qualitatively for C. albicans/C. tropicalis, C. glabrata/C. krusei, and C. parapsilosis . T2Candida and cBCs were positive if they detected a species present in the dBC. Results: Median time between collection of dBC and T2Candida/cBC samples in 152 patients was 55.5 hours (range, 16.4–148.4). T2Candida and cBCs were positive in 45% (69/152) and 24% (36/152) of patients, respectively ( P < .0001). T2Candida clinical sensitivity was 89%, as positive results were obtained in 32/36 patients with positive cBCs. Combined test results were both positive (T2+/cBC+), 21% (32/152); T2+/cBC−, 24% (37/152); T2−/cBC+, 3% (4/152); and T2−/cBC−, 52% (79/152). Prior antifungal therapy, neutropenia, and C. albicans candidemia were independently associated with T2Candida positivity and T2+/cBC− results ( P values < .05). Conclusions: T2Candida was sensitive for diagnosing candidemia at the time of positive blood cultures. In patients receiving antifungal therapy, T2Candida identified bloodstream infections that were missed by cBCs. T2Candida may improve care by shortening times to Candida detection and species identification compared to blood cultures, retaining sensitivity during antifungal therapy and rendering active candidemia unlikely if results are negative. Clinical Trials Registration: NCT01525095.